General and abdominal obesity and risk of esophageal and gastric adenocarcinoma in the European Prospective Investigation into Cancer and Nutrition. Issue 3 (9th February 2015) - Steffen, Annika; Huerta, José‐Maria; Weiderpass, Elisabete; Bueno‐de‐Mesquita, H.B(as); May, Anne M.; Siersema, Peter D.; Kaaks, Rudolf; Neamat‐Allah, Jasmine; Pala, Valeria; Panico, Salvatore; Saieva, Calogero; Tumino, Rosario; et al.
<x xml:space="preserve">Abstract</x> General obesity, as reflected by BMI, is an established risk factor for esophageal adenocarcinoma (EAC), a suspected risk factor for gastric cardia adenocarcinoma (GCC) and appears unrelated to gastric non‐cardia adenocarcinoma (GNCC). How abdominal obesity, as commonly measured by waist circumference (WC), relates to these cancers remains largely unexplored. Using measured anthropometric data from 391, 456 individuals from the European Prospective Investigation into Cancer and Nutrition (EPIC) study and 11 years of follow‐up, we comprehensively assessed the association of anthropometric measures with risk of EAC, GCC and GNCC using multivariable proportional hazards regression. One hundred twenty‐four incident EAC, 193 GCC and 224 GNCC were accrued. After mutual adjustment, BMI was unrelated to EAC, while WC showed a strong positive association (highest vs. lowest quintile HR = 1.19; 95% CI, 0.63–2.22 and HR = 3.76; 1.72–8.22, respectively). Hip circumference (HC) was inversely related to EAC after controlling for WC, while WC remained positively associated (HR = 0.35; 0.18–0.68, and HR=4.10; 1.94‐8.63, respectively). BMI was not associated with GCC or GNCC. WC was related to higher risks of GCC after adjustment for BMI and more strongly after adjustment for HC (highest vs. lowest quintile HR = 1.91; 1.09–3.37, and HR = 2.23; 1.28–3.90, respectively). Our study demonstrates that abdominal, rather than general, obesity is an indisputable risk factor for EAC and also provides evidence for a protective effect of gluteofemoral (subcutaneous) adipose tissue in EAC. Our study further shows that general obesity is not a risk factor for GCC and GNCC, while the role of abdominal obesity in GCC needs further investigation.